Schwarzschild-type black holes in Starobinsky-Bel-Robinson gravity - Ruben Campos Delgado; Sergei V. Ketov (Physics Letters B, 2023)
We study physical properties of a Schwarzschild-type black hole in the framework of the recently proposed Starobinsky-Bel-Robinson (SBR) modified theory of gravity, working perturbatively in the coupling constant. In particular, we compute the temperature, entropy, pressure and lifetime of a Schwarzschild-type black hole.